PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI TANAH KAVLING BUKIT PALM SINGHASARI MALANG - Ikrom, Moechammad Fadhli Dzil; Pradiani, Theresia (Jurnal Manajemen dan Profesional, 2023)
This research is motivated by rapid population growth, so the need for housing increases. This study aimed to determine the effect of price and location on purchasing decisions through an interest in buying plots of land at PT. Palm Singhasari Hill, Malang. The method used in this study is quantitative, with the population being clients who have purchased tracts of land. With a sample using the Purposive Sampling Technique with 100 people. Data collection techniques using a questionnaire. The results of this study indicate that price has a positive and significant influence on the decision to purchase PT. Bukit Palm Singhasari Malang's location has a negative and insignificant impact on the decision to acquire PT. Bukit Palm Singhasari Malang, the price has a negative and little effect on the intention to buy PT. Bukit Palm Singhasari Malang's location positively and significantly influences the choise to buy PT. Bukit Palm Singhasari Malang, buying interest positively and significantly influences the decision to buy PT. Bukit Palm Singhasari Malang, the price has a negative and insignificant influence on purchasing decisions through an interest in buying PT. Bukit Palm Singhasari Malang, location positively and significantly influences purchasing decisions through n interest in buying PT. Palm Singhasari Hill, Malang.